2022
DOI: 10.3389/fcimb.2022.1011378
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchis sinensis infection induces hepatobiliary injury via disturbing sphingolipid metabolism and activating sphingosine 1-phosphate receptor 2

Abstract: Clonorchis sinensis (C. sinensis) infection induces severe hepatobiliary injuries, which can cause inflammation, periductal fibrosis, and even cholangiocarcinoma. Sphingolipid metabolic pathways responsible for the generation of sphingosine-1-phosphate (S1P) and its receptor S1P receptors (S1PRs) have been implicated in many liver-related diseases. However, the role of S1PRs in C. sinensis-mediated biliary epithelial cells (BECs) proliferation and hepatobiliary injury has not been elucidated. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…CK-19 keratin has been shown to be a marker for the diagnosis and identi cation of hepatocellular carcinoma cells [30]. Recent evidence pinpoints that Clonorchis sinensis infection could lead to the increased expression of CK-19 in hepatocyte and hepatobiliary tissues [8,41]. In agreement with these report, we also demonstrated that the expression level of CK-19 keratin in hepatic tissue was elevated in rat with chronic Clonorchis sinensis infection.…”
Section: Discussionsupporting
confidence: 90%
“…CK-19 keratin has been shown to be a marker for the diagnosis and identi cation of hepatocellular carcinoma cells [30]. Recent evidence pinpoints that Clonorchis sinensis infection could lead to the increased expression of CK-19 in hepatocyte and hepatobiliary tissues [8,41]. In agreement with these report, we also demonstrated that the expression level of CK-19 keratin in hepatic tissue was elevated in rat with chronic Clonorchis sinensis infection.…”
Section: Discussionsupporting
confidence: 90%
“…sinensis is a prominent food-borne parasite prevalent in regions such as China, particularly in Guangxi, Guangdong, Heilongjiang and Liaoning [ 12 , 29 ]. This parasite has been associated with various hepatobiliary system injuries, encompassing inflammation, periductal fibrosis, cholangiocarcinoma, and even HCC [ 20 , 30 ]. While a substantial body of evidence links clonorchiasis to cholangiocarcinoma [ 18 , 31 , 32 ], the connection between clonorchiasis and HCC is less acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epidemiological and clinical studies have unveiled disconcerting links between C. sinensis infection and the prognosis of HCC patients, suggesting that it may serve as a substantial risk factor for HCC [10]. The carcinogenesis of C. sinensis infection involves various factors, such as mechanical obstruction and damage to the biliary barrier system, consisting of infectionrelated inflammation, pathological effects from excretory-secretory products (ESPs), enhanced features of epithelial-mesenchymal transition, and immunopathology imbalance [10,[19][20][21]. However, the intricate mechanisms underlying C. sinensis's contribution to HCC development remain incompletely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma to biliary epithelium causes ulceration and desquamation, and results in typical pathological findings of periductal fibrosis, epithelial hyperplasia and glandular metaplasia. 6 Chronic infection can lead to clinical manifestations beyond acute phase infection such as biliary obstruction, stone formation, cholecystitis, cholangitis, hepatitis, and cirrhosis. 7 Structural changes include hepatomegaly, biliary ductal dilatation, and stricture formation.…”
Section: Discussionmentioning
confidence: 99%